HUBUNGAN ANTARA KOMITMEN PROFESIONAL DAN SOSIALISASI ANTISIPATIF DENGAN ORIENTASI ETIKA MAHASISWA AKUNTANSI - Edi Joko Setyadi (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2010)
The purpose of this study is to analize the relationships between the professionalcommitment and anticipatory socialization with accounting students` ethical orientation by used the perception of the importance of financial responsibility to a proxy of anticipatory socialization. The  data of the study was collected from the Accounting students of University in the Central Java who completed and returned the questionnaires. The data was gotten by distributing the questionnaires directly to the students, by snowballing and post mail. 400questionnaires was distributed and 183 of them (45,75%) was used as the analysis samples. The data analysis used was correlation and t-test in SPSS.The result showed that professional commitment have no relationships with ethical perceptions and ethical intentions. The result also showed that accounting students` ethical perceptions is different for a few audit vignette with high level of ambiguity. Besides, in this research, the result also showed that accounting students` ethical intentions is not different for a few audit vignette because appearable social desirability to adjust and fit perceived ethical norms.